Soil pollution : origin, monitoring and remediation - Mirsal, Ibrahim A. ([Place of publication not identifed] : Springer-verlag Berlin And Hei, 2010)
Despite having been published about two years ago for the first time, the continuous demand for this book encouraged me to prepare this revised and enlarged edition.
Soil - Its Nature and Origin.- The Origin of Soil.- Soil Constituents.- Soil Properties.- Soil Types and Classification.- Soil Degradation.- Soil Pollution.- Major Types of Soil Pollutants.- Sources of Soil Pollution.- Pollution Mechanisms and Soil-Pollutants Interaction.- Pollutants' Alteration, Transformation, and Initiation of Chemical Changes within the Soil.- Monitoring of Soil Pollution.- Monitoring and Monitoring Plans.- Biological Monitoring.- Modelling of Soil Pollution.- Models and Their Construction.- Soil Remediation.- Planning and Realisation of Soil Remediation.
Includes bibliographical references and index.
Keywords: ECOLOGY -- SOIL POLLUTION -- PEDOLOGY -- TYPES OF POLLUTION -- SOURCES OF POLLUTION -- BIOLOGICAL CONTROL